К вопросу образования двойников ставролита в метаморфических породах (на примере кристаллических сланцев Кейв, Кольский п-ов) - Нерадовский, Ю.Н. (Мінералогічний журнал, 2011)
Исследован механизм зарождения и формирования двойников ставролита в кристаллических плагиоклазставролитовых сланцах. Показано, что образование двойников в рассматриваемых метаморфических породах
происходило в результате механического воздействия на зародыши ставролита растягивающих сил пластического "течения" сланцев в процессе их формирования. Внутреннее строение двойников отражает метаморфизм
сланцев и помогает восстановить динамику развития процесса. Досліджено механізм зародження і формування двійників ставроліту в кристалічних плагіоклаз-ставролітових сланцях. Показано, що утворення двійників у
цих метаморфічних породах відбувалося внаслідок механічної дії розтягувальних сил пластичної "течії"
сланців на зародки ставроліту в процесі їх формування. Внутрішня будова двійників відображає метаморфізм сланців і допомагає відновити динаміку розвитку процесу. The genesis of staurolite twins in crystalline plagioclasestaurolite
schists of the Keivy schists (the Kola Peninsula)
has been studied. It is shown that the twins in the metamorphic
rocks under question have formed as a result of
staurolite nuclei, being mechanically affected by stretching
forces of an elastic "flow" of schists during their formation.
The twins structure reflects metamorphism of the schists
and helps restore the process dynamics. A peculiar feature
of staurolite in the studied rocks is its zoning, remarkably
distinct in every crystal. A special paper is dedicated to the
study of the zoning. Major elements of zonal crystals are a
nucleus and two I-genus zones. A thin II-genus zoning is
developed in I-genus zones. The structure of staurolite
crystals allows defining three stages of its formation. The
first stage is characterized by the formation of nuclei, i. e.
the embryos of future staurolite crystals on the initial stage
of the crystalline schists formation as a result of metamorphic
reaction. The second stage of the staurolite crystallization
comprises the nucleus stretching and the second
zone forming. The way the crystal grew in this period depended
on the crystal space orientation. The motive forces
for the crystals growth at the second stage were deformations
of the comprising environment given to the "flow"
and deformation of the mineral as a "participant perceiving
external stresses". It is assumed that the nucleus
stretching deformation in the direction of the schists "flow"
occurred under the effect of forces of the elastic schist
flow. During the stretching deformation the nucleus elongated
with no continuity break or divided into two parts,
both of these parts being remote from the long crystal axis.
In the first case the twinning took place in a number of
crystals. It is supposed that the stretching of crystals with
no continuity break resulted from the nucleus material deformation
according to the cell "migration of dislocations"
and translation gliding. The latter is accompanied by healing
of defects. The first signs of the twinning are observed
at the boundaries of a staurolite crystal nucleus. A wedgelike
incision with a twin embryo is observed on the nucleus
of twin crystals. The embryo was initially oriented according
to either {231} or {031}, which resulted in the formation
of an oblique or cruciform twin. The crystal-2 happened
to originate not on two sides of the crystal-1, but on
one side. The opposite half of the crystal-2 was formed
later. However, the crystal preserved its space orientation
on a plane, which provided the suggestion that a "through"
twinning plane existed in the crystal-1 during the crystal-2
origination. Interestingly, the twinning joint is always close
to the heart of the intergrown crystals. Thus, crystals in
staurolite twins originated at different times and it is necessary
to distinguish crystal-1 and crystal-2. Depending
on the orientation according to {231} or {031}, crystal-2
grew and crossed the nucleus of the host crystal obliquely
of perpendicularly. The third stage of the staurolite crystallization
is characterized by regular tectonic conditions and
a growth of crystals in all directions. Once the nucleus
stopped stretching and the second zone crystallized, the
formation of twins finished. All crystals, including twin
ones, got overgrown by planes of the third zone, i. e. obtained
the current shape.